Corriere Illustrato, Domenica, La Spedizione Andrée - Unknown (Massachusetts Institute of Technology. Libraries. Department of Distinctive Collections, 1899)
Italian newspaper with an article about the fatal North Pole balloon expedition of Salomon Andrée (on page 165). An accompanying illustration shows the balloon sailing over icebergs, with an inset image of the explorer Andrée, and an illustration of the interior of the balloon car (cross-section). For more information about this item, visit https://archivesspace.mit.edu/repositories/2/digital_objects/792